2011
DOI: 10.1097/coc.0b013e3181cae8dd
|View full text |Cite
|
Sign up to set email alerts
|

Value of Tumor Size as a Prognostic Variable in Colorectal Cancer

Abstract: Tumor size proved to be an independent prognostic parameter for patients with colorectal cancer. Optimal cut-off values vary among different parts of the large bowel. Whereas prognostic significance is strong within the colon, it appears to be of minor value within the rectum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
71
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 25 publications
15
71
4
Order By: Relevance
“…These tumors are diagnosed in the early stages with the technological improvement and common use of colonoscopy, but the problem is still going on. Several studies emphasized that larger tumors are more frequent in the right colon (2,20,21). We also found that proximal tumor cancers tended to have a larger diameter.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…These tumors are diagnosed in the early stages with the technological improvement and common use of colonoscopy, but the problem is still going on. Several studies emphasized that larger tumors are more frequent in the right colon (2,20,21). We also found that proximal tumor cancers tended to have a larger diameter.…”
Section: Discussionsupporting
confidence: 65%
“…According to our data, we found that there was a significant statistical relationship between the size of the horizontal diameter and lymph node invasion; large tumors were associated with more positive lymph nodes. Although some studies in the literature support our data (2,19,24), other studies concluded that the size of the horizontal diameter is not an important factor in determining lymph node involvement (18,20,25).…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…However, in our cohort, just the increased tumor size in CRC was closely correlated with the high expression of STYK1/NOK. Although the increased tumor size in CRC was not part of the staging system, previous studies have suggested that tumor size is also an important prognostic factor in CRC (Kornprat et al, 2011). Thus, collectively, STYK1/NOK might be important biological marker in carcinogenesis of CRC and the high expression of STYK1/NOK may contribute to the proliferation of CRC tissues.…”
Section: Discussionmentioning
confidence: 99%